Relationship of postprandial fibroblast growth factor 21 with lipids, inflammation and metabolic dysfunction-associated fatty liver disease during oral fat tolerance test - Li, Xiaolong; Zheng, Kunjie; Liu, Lifang; Zhang, Tingxue; Gu, Wei; Hou, Xiaoyu; Geng, Jianlin; Song, Guangyao (Frontiers in Endocrinology, 2024)
Introduction: Metabolic dysfunction-associated fatty liver disease (MAFLD) is closely associated with serum fibroblast growth factor (FGF) 21; however, previous studies have typically focused on the static fasting state, and the relationships between postprandial FGF21 levels, postprandial metabolic status, and MAFLD remain unclear. Therefore, we measured postprandial lipids, inflammatory factors, and FGF21 levels in MAFLD and further analyzed their relationship using an oral fat tolerance test (OFTT).In total, 103 non-diabetic adult volunteers, including 46 patients with MAFLD, were included in this study. All participants underwent the OFTT. Venous blood samples were collected at 0, 2, 4, and 6 h. Circulating total cholesterol (TC), triglyceride (TG), free fatty acid (FFA) , high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C) , interleukin-6(IL-6), tumor necrosis factor-α(TNF-α), hypersensitive-C reactive protein(hs-CRP) and FGF21 were assessed.Results: Serum FGF21 significantly increased in the fasting state (P < 0.05) and showed a biphasic change of first decreasing and then increasing in MAFLD during the OFTT . The postprandial levels of TG, TC, LDL-C, FFA, IL-6, TNF-α and hs-CRP were significantly increased in MAFLD (P < 0.05). After adjusting for multiple factors, the FGF21 incremental area under the curve (iAUC) was linearly correlated with the FFA iAUC, TG iAUC, and IL-6 iAUC (P < 0.05) and was an independent factor for MAFLD (P < 0.05, OR=1.403).Conclusions: Dyslipidemia and excessive inflammation in MAFLD are associated to FGF21 levels in the postprandial period. An abnormal postprandial FGF21 response may be an important mechanism of MAFLD.